Penggunaan Metode Pembelajaran Seminar Paidea Untuk Meningkatkan Hasil Belajar Siswa - Nanda Akhmad Romadhon, Dwi; Nofriansyah, Nofriansyah; Supriatna, Endang; Rahayu, Sri; Ahman, Eeng (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
This study aims to enhance student learning outcomes in social studies, specifically on the topic of Socio-Cultural Change, using the Paidea Seminar method. The research is classified as classroom action research, consisting of two cycles. Each cycle includes four stages: action planning, action implementation, observation/evaluation, and reflection. The research was conducted in class IXA at SMPN 27 Tanjung Jabung Timur, involving 20 students for the 2023/2024 academic year. Data on student learning outcomes were collected through tests and analyzed descriptively. The findings indicate that (1) there is an increase in student learning outcomes, with an average score rising from 67.25 and a classical learning completeness of 50% in the first cycle to an average score of 76 and a classical learning completeness of 85% in the second cycle.